Recall that in Remark 14.1.23, we learned to calculate the cube root of a number, say \(\sqrt[3]{8}\text{,}\) we can type 8^(1/3) into a calculator. This suggests that \(\sqrt[3]{8}=8^{\sfrac{1}{3}}\text{.}\) In this section, we will learn why this is true, and how to simplify expressions with rational exponents.
Many learners will find a review of exponent rules to be helpful before continuing with the current section. Section 2.9 covers an introduction to exponent rules, and there is more in Section 6.1. The basic rules are summarized in List 6.1.15. These rules are still true and we can use them throughout this section whenever they might help.
Figure14.2.1 Alternative Video Lesson
Subsection14.2.1Radical Expressions and Rational Exponents
Additionally, if \(n\) is an odd natural number, then even when \(a\) is negative, we still have \(a^{\sfrac{1}{n}}=\sqrt[n]{a}\text{.}\)
Warning14.2.3Exponents on Negative Bases
Some computers and calculators follow different conventions when there is an exponent on a negative base. To see an example of this, visit WolframAlpha and try entering cuberoot(-8), and then try (-8)^(1/3), and you will get different results. cuberoot(-8) will come out as \(-2\text{,}\) but (-8)^(1/3) will come out as a certain non-real complex number. Most likely, the graphing technology you are using does behave as in Fact 14.2.2, but you should confirm this.
With this relationship, we can re-write radical expressions as expressions with rational exponents.
Example14.2.4
Evaluate \(\sqrt[4]{9}\) with a calculator. Round your answer to two decimal places.
Since \(\sqrt[4]{9}=9^{\sfrac{1}{4}}\text{,}\) we press the following buttons on a calculator to get the value: 9^(1/4). So, we see that \(\sqrt[4]{9}\approx1.73\text{.}\)
For many examples that follow, we will not need a calculator. We will, however, need to recognize the roots in Table 14.2.5.
Square Roots
Cube Roots
\(4^{th}\)-Roots
\(5^{th}\)-Roots
Roots of Powers of \(2\)
\(\sqrt{1}=1\)
\(\sqrt[3]{1}=1\)
\(\sqrt[4]{1}=1\)
\(\sqrt[5]{1}=1\)
\(\sqrt{4}=2\)
\(\sqrt[3]{8}=2\)
\(\sqrt[4]{16}=2\)
\(\sqrt[5]{32}=2\)
\(\sqrt{4}=2\)
\(\sqrt{9}=3\)
\(\sqrt[3]{27}=3\)
\(\sqrt[4]{81}=3\)
\(\sqrt[3]{8}=2\)
\(\sqrt{16}=4\)
\(\sqrt[3]{64}=4\)
\(\sqrt[4]{16}=2\)
\(\sqrt{25}=5\)
\(\sqrt[3]{125}=5\)
\(\sqrt[5]{32}=2\)
\(\sqrt{36}=6\)
\(\sqrt[6]{64}=2\)
\(\sqrt{49}=7\)
\(\sqrt[7]{128}=2\)
\(\sqrt{64}=8\)
\(\sqrt[8]{256}=2\)
\(\sqrt{81}=9\)
\(\sqrt[9]{512}=2\)
\(\sqrt{100}=10\)
\(\sqrt[10]{1024}=2\)
\(\sqrt{121}=11\)
\(\sqrt{144}=12\)
Table14.2.5 Small Roots of Appropriate Natural Numbers
Example14.2.6
Convert the radical expression \(\sqrt[3]{5}\) into an expression with a rational exponent and simplify it if possible.
\(\sqrt[3]{5}=5^{\sfrac{1}{3}}\text{.}\) No simplification is possible since the cube root of \(5\) is not a perfect integer appearing in Table 14.2.5.
Example14.2.7
Write the expressions in radical form using Fact 14.2.2 and simplify the results.
Fact 14.2.2 applies to variables in expressions just as much as it does to numbers.
Remark14.2.8
In general, it is easier to do algebra with rational exponents on variables than with radicals of variables. You should use Fact 14.2.2 to convert from rational exponents to radicals on variables only as a last step in simplifying.
Example14.2.9
Write the expressions as simplified as they can be using radicals.
Note that in this example the exponent is only applied to the \(x\text{.}\) Making this type of observation should be our first step for each of these exercises.
\begin{align*}
2x^{-\sfrac{1}{2}}\amp=\frac{2}{x^{\sfrac{1}{2}}} \amp\amp\text{by the }\knowl{./knowl/item-exponent-rules-negative-exponent-definition.html}{\text{Negative Exponent Rule}}\\
\amp=\frac{2}{\sqrt{x}} \amp\amp\text{by the } \knowl{./knowl/fact-rational-exponent-rule-i.html}{\text{Radicals and Rational Exponents Rule}}
\end{align*}
In this exercise, the exponent applies to both the \(5\) and \(x\text{.}\)
\begin{align*}
(5x)^{\sfrac{1}{3}}\amp=\sqrt[3]{5x} \amp\amp\text{by the } \knowl{./knowl/fact-rational-exponent-rule-i.html}{\text{Radicals and Rational Exponents Rule}}
\end{align*}
We could choose to simplify our answer in a different way. Note that neither one is technically preferred over the other except that perhaps the first way is simpler.
\begin{align*}
(5x)^{\sfrac{1}{3}}\amp=5^{\sfrac{1}{3}}x^{\sfrac{1}{3}} \amp\amp\text{by the } \knowl{./knowl/item-exponent-rules-product-to-a-power.html}{\text{Product to a Power Rule}}\\
\amp=\sqrt[3]{5}\sqrt[3]{x} \amp\amp\text{by the } \knowl{./knowl/fact-rational-exponent-rule-i.html}{\text{Radicals and Rational Exponents Rule}}
\end{align*}
As in the previous exercise, we have a choice as to how to simplify this expression. Here we should note that we do know what the cube root of \(-27\) is, so we will take the path to splitting up the expression, using the Product to a Power Rule, before applying the root.
\begin{align*}
\left(-27x^{12}\right)^{\sfrac{1}{3}}\amp=(-27)^{\sfrac{1}{3}}\cdot \left(x^{12}\right)^{\sfrac{1}{3}}\amp\amp\text{by the } \knowl{./knowl/item-exponent-rules-product-to-a-power.html}{\text{Product to a Power Rule}}\\
\amp=(-27)^{\sfrac{1}{3}}\cdot \left(x^{12\cdot\sfrac{1}{3}}\right) \amp\amp\text{by the } \knowl{./knowl/item-exponent-rules-power-to-a-power.html}{\text{Power to a Power Rule}}\\
\amp=\sqrt[3]{-27}\cdot x^4 \amp\amp\text{by the } \knowl{./knowl/fact-rational-exponent-rule-i.html}{\text{Radicals and Rational Exponents Rule}}\\
\amp=-3x^4
\end{align*}
We'll use the exponent rule for a fraction raised to a power.
\begin{align*}
\left(\frac{16x}{81y^8}\right)^{\sfrac{1}{4}}\amp=\frac{\left(16x\right)^{\sfrac{1}{4}}}{\left(81y^8\right)^{\sfrac{1}{4}}} \amp\amp\text{by the } \knowl{./knowl/item-exponent-rules-quotient-to-a-power.html}{\text{Quotient to a Power Rule}}\\
\amp=\frac{16^{\sfrac{1}{4}}\cdot x^{\sfrac{1}{4}}}{81^{\sfrac{1}{4}} \cdot \left(y^8\right)^{\sfrac{1}{4}}} \amp\amp\text{by the } \knowl{./knowl/item-exponent-rules-product-to-a-power.html}{\text{Product to a Power Rule}}\\
\amp=\frac{16^{\sfrac{1}{4}}\cdot x^{\sfrac{1}{4}}}{81^{\sfrac{1}{4}}\cdot y^2}\\
\amp=\frac{\sqrt[4]{16}\cdot \sqrt[4]{x}}{\sqrt[4]{81}\cdot y^2} \amp\amp\text{by the } \knowl{./knowl/fact-rational-exponent-rule-i.html}{\text{Radicals and Rational Exponents Rule}}\\
\amp=\frac{2\sqrt[4]{x}}{3y^2}
\end{align*}
Fact 14.2.2 describes what can be done when there is a fractional exponent and the numerator is a \(1\text{.}\) The numerator doesn't have to be a \(1\) though and we need guidance for that situation.
Fact14.2.10Radicals and Rational Exponents Rule
If \(m\) and \(n\) are natural numbers such that \(\frac{m}{n}\) is a reduced fraction, and \(a\) is any non-negative real number or function that takes non-negative values, then
Additionally, if \(n\) is an odd natural number, then even when \(a\) is negative, we still have \(a^{\sfrac{m}{n}}=\sqrt[n]{a^m}=\left(\sqrt[n]{a}\right)^m\text{.}\)
Remark14.2.11
By Fact 14.2.10, there are two ways to express \(a^{\sfrac{m}{n}}\) as a radical, both
There are different times to use each formula. In general, use \(a^{\sfrac{m}{n}}=\sqrt[n]{a^m}\) for variables and \(a^{\sfrac{m}{n}}=\left(\sqrt[n]{a}\right)^m\) for numbers.
Example14.2.12
Consider the expression \(27^{\sfrac{4}{3}}\text{.}\) Use both versions of Fact 14.2.10 to explain part of Remark 14.2.11.
Consider the expression \(x^{\sfrac{4}{3}}\text{.}\) Use both versions of Fact 14.2.10 to explain the other part of Remark 14.2.11.
The expression \(27^{\sfrac{4}{3}}\) can be evaluated in the following two ways by Fact 14.2.10.
\begin{align*}
27^{\sfrac{4}{3}}\amp=\sqrt[3]{27^4}\amp\amp\text{by the first part of the } \knowl{./knowl/fact-rational-exponent-rule-ii.html}{\text{Radicals and Rational Exponents Rule}}\\
\amp=\sqrt[3]{531441}\\
\amp=81\\
\amp\amp\text{or}\\
27^{\sfrac{4}{3}}\amp=\left(\sqrt[3]{27}\right)^4\amp\amp\text{by the second part of the } \knowl{./knowl/fact-rational-exponent-rule-ii.html}{\text{Radicals and Rational Exponents Rule}}\\
\amp=3^4\\
\amp=81
\end{align*}
The calculations using \(a^{\sfrac{m}{n}}=\left(\sqrt[n]{a}\right)^m\) worked with smaller numbers and can be done without a calculator. This is why we made the general recommendation in Remark 14.2.11.
The expression \(x^{\sfrac{4}{3}}\) can be evaluated in the following two ways by Fact 14.2.10.
\begin{align*}
x^{\sfrac{4}{3}}\amp=\sqrt[3]{x^4}\amp\amp\text{by the first part of } \knowl{./knowl/fact-rational-exponent-rule-ii.html}{\text{Radicals and Rational Exponents Rule}}\\
\amp\amp\text{or}\\
x^{\sfrac{4}{3}}\amp=\left(\sqrt[3]{x}\right)^4\amp\amp\text{by the second part of the } \knowl{./knowl/fact-rational-exponent-rule-ii.html}{\text{Radicals and Rational Exponents Rule}}
\end{align*}
In this case, the simplification using \(a^{\sfrac{m}{n}}=\sqrt[n]{a^m}\) is just shorter looking and easier to write. This is why we made the general recommendation in Remark 14.2.11.
\begin{align*}
8^{\sfrac{2}{3}}\amp=\left(\sqrt[3]{8}\right)^2\amp\amp\text{by the second part of the } \knowl{./knowl/fact-rational-exponent-rule-ii.html}{\text{Radicals and Rational Exponents Rule}}\\
\amp=2^2\\
\amp=4
\end{align*}
\begin{align*}
16^{-\sfrac{3}{2}}\amp=\frac{1}{16^{\sfrac{3}{2}}}\amp\amp\text{by the } \knowl{./knowl/item-exponent-rules-negative-exponent-definition.html}{\text{Negative Exponent Rule}}\\
\amp=\frac{1}{\left(\sqrt{16}\right)^3}\amp\amp\text{by the second part of the } \knowl{./knowl/fact-rational-exponent-rule-ii.html}{\text{Radicals and Rational Exponents Rule}}\\
\amp=\frac{1}{4^3}\\
\amp=\frac{1}{64}
\end{align*}
\begin{align*}
-16^{\sfrac{3}{4}}\amp=-\left(\sqrt[4]{16}\right)^3 \amp\amp\text{by the second part of the } \knowl{./knowl/fact-rational-exponent-rule-ii.html}{\text{Radicals and Rational Exponents Rule}}\\
\amp=-2^3\\
\amp=-8
\end{align*}
In this problem the negative can be associated with either the numerator or the denominator, but not both. We choose the numerator.
\begin{align*}
\left(-\frac{27}{64}\right)^{\sfrac{2}{3}}\amp=\left(\sqrt[3]{-\frac{27}{64}}\right)^2 \amp\amp\text{by the second part of the } \knowl{./knowl/fact-rational-exponent-rule-ii.html}{\text{Radicals and Rational Exponents Rule}}\\
\amp=\left(\frac{\sqrt[3]{-27}}{\sqrt[3]{64}}\right)^2\\
\amp=\left(\frac{-3}{4}\right)^2\\
\amp=\frac{(-3)^2}{(4)^2}\\
\amp=\frac{9}{16}
\end{align*}
While we are looking at the algebra of \(x^{\sfrac{m}{n}}\text{,}\) we should briefly examine a graph to see what this type of function can look like. Fractional powers can make some fairly interesting graphs. We invite you to play with these graphs on your favorite graphing program.
\begin{align*}
\frac{1}{\sqrt{x}}\amp=\frac{1}{x^{\sfrac{1}{2}}}\amp\amp\text{by the } \knowl{./knowl/fact-rational-exponent-rule-i.html}{\text{Radicals and Rational Exponents Rule}}\\
\amp=x^{-\sfrac{1}{2}}\amp\amp\text{by the } \knowl{./knowl/item-exponent-rules-negative-exponent-definition.html}{\text{Negative Exponent Rule}}
\end{align*}
\begin{align*}
\frac{1}{\sqrt[3]{25}}\amp=\frac{1}{25^{\sfrac{1}{3}}}\amp\amp\text{by the } \knowl{./knowl/fact-rational-exponent-rule-i.html}{\text{Radicals and Rational Exponents Rule}}\\
\amp=\frac{1}{\left(5^2\right)^{\sfrac{1}{3}}}\\
\amp=\frac{1}{5^{2\cdot\sfrac{1}{3}}}\amp\amp\text{by the } \knowl{./knowl/item-exponent-rules-power-to-a-power.html}{\text{Power to a Power Rule}}\\
\amp=\frac{1}{5^{\sfrac{2}{3}}}\\
\amp=5^{-\sfrac{2}{3}}\amp\amp\text{by the } \knowl{./knowl/item-exponent-rules-negative-exponent-definition.html}{\text{Negative Exponent Rule}}
\end{align*}
Learners of these simplifications often find it challenging, so we now include a plethora of examples of varying difficulty.
Example14.2.17
Use exponent properties in List 14.2.15 to simplify the expressions, and write all final versions using radicals.
\begin{align*}
2w^{\sfrac{7}{8}}\amp=2\sqrt[8]{w^7}\amp\amp\text{by the } \knowl{./knowl/fact-rational-exponent-rule-ii.html}{\text{Radicals and Rational Exponents Rule}}
\end{align*}
\begin{align*}
\frac{1}{2}y^{-\sfrac{1}{2}}\amp=\frac{1}{2}\frac{1}{y^{\sfrac{1}{2}}}\amp\amp\text{by the } \knowl{./knowl/item-exponent-rules-negative-exponent-definition.html}{\text{Negative Exponent Rule}}\\
\amp=\frac{1}{2}\frac{1}{\sqrt{y}}\amp\amp\text{by the } \knowl{./knowl/fact-rational-exponent-rule-ii.html}{\text{Radicals and Rational Exponents Rule}}\\
\amp=\frac{1}{2\sqrt{y}}
\end{align*}
\begin{align*}
\left(27b\right)^{\sfrac{2}{3}}\amp=\left(27\right)^{\sfrac{2}{3}}\cdot\left(b\right)^{\sfrac{2}{3}}\amp\amp\text{by the } \knowl{./knowl/item-exponent-rules-product-to-a-power.html}{\text{Product to a Power Rule}}\\
\amp=\left(\sqrt[3]{27}\right)^2\cdot\sqrt[3]{b^2}\amp\amp\text{by the } \knowl{./knowl/fact-rational-exponent-rule-ii.html}{\text{Radicals and Rational Exponents Rule}}\\
\amp=3^2\cdot\sqrt[3]{b^2}\\
\amp=9\sqrt[3]{b^2}
\end{align*}
\begin{align*}
\left(-8p^6\right)^{\sfrac{5}{3}}\amp=\left(-8\right)^{\sfrac{5}{3}}\cdot\left(p^6\right)^{\sfrac{5}{3}}\amp\amp\text{by the } \knowl{./knowl/item-exponent-rules-product-to-a-power.html}{\text{Product to a Power Rule}}\\
\amp=\left(-8\right)^{\sfrac{5}{3}}\cdot p^{6\cdot\sfrac{5}{3}}\amp\amp\text{by the } \knowl{./knowl/item-exponent-rules-power-to-a-power.html}{\text{Power to a Power Rule}}\\
\amp=\left(\sqrt[3]{-8}\right)^5\cdot p^{10}\amp\amp\text{by the } \knowl{./knowl/fact-rational-exponent-rule-ii.html}{\text{Radicals and Rational Exponents Rule}}\\
\amp=(-2)^5\cdot p^{10}\\
\amp=-32p^{10}
\end{align*}
\begin{align*}
\sqrt{x^3}\cdot\sqrt[4]{x}\amp=x^{\sfrac{3}{2}}\cdot x^{\sfrac{1}{4}}\amp\amp\text{by the } \knowl{./knowl/fact-rational-exponent-rule-ii.html}{\text{Radicals and Rational Exponents Rule}}\\
\amp=x^{\sfrac{3}{2}+\sfrac{1}{4}}\amp\amp\text{by the } \knowl{./knowl/item-exponent-rules-product.html}{\text{Product Rule}}\\
\amp=x^{\sfrac{6}{4}+\sfrac{1}{4}}\\
\amp=x^{\sfrac{7}{4}}\\
\amp=\sqrt[4]{x^7}\amp\amp\text{by the } \knowl{./knowl/fact-rational-exponent-rule-ii.html}{\text{Radicals and Rational Exponents Rule}}
\end{align*}
\begin{align*}
h^{\sfrac{1}{3}}+h^{\sfrac{1}{3}}+h^{\sfrac{1}{3}}\amp=3h^{\sfrac{1}{3}}\\
\amp=3\sqrt[3]{h}\amp\amp\text{by the } \knowl{./knowl/fact-rational-exponent-rule-i.html}{\text{Radicals and Rational Exponents Rule}}
\end{align*}
\begin{align*}
\frac{\sqrt{z}}{\sqrt[3]{z}}\amp=\frac{z^{\sfrac{1}{2}}}{z^{\sfrac{1}{3}}}\amp\amp\text{by the } \knowl{./knowl/fact-rational-exponent-rule-i.html}{\text{Radicals and Rational Exponents Rule}}\\
\amp=z^{\sfrac{1}{2}-\sfrac{1}{3}}\amp\amp\text{by the } \knowl{./knowl/item-exponent-rules-quotient.html}{\text{Quotient Rule}}\\
\amp=z^{\sfrac{3}{6}-\sfrac{2}{6}}\\
\amp=z^{\sfrac{1}{6}}\\
\amp=\sqrt[6]{z}\amp\amp\text{by the } \knowl{./knowl/fact-rational-exponent-rule-i.html}{\text{Radicals and Rational Exponents Rule}}
\end{align*}
\begin{align*}
\sqrt{\sqrt[4]{q}}\amp=\sqrt{q^{\sfrac{1}{4}}}\amp\amp\text{by the } \knowl{./knowl/fact-rational-exponent-rule-i.html}{\text{Radicals and Rational Exponents Rule}}\\
\amp=\left(q^{\sfrac{1}{4}}\right)^{\sfrac{1}{2}}\amp\amp\text{by the } \knowl{./knowl/fact-rational-exponent-rule-i.html}{\text{Radicals and Rational Exponents Rule}}\\
\amp=q^{\sfrac{1}{4}\cdot\sfrac{1}{2}}\amp\amp\text{by the } \knowl{./knowl/item-exponent-rules-power-to-a-power.html}{\text{Power to a Power Rule}}\\
\amp=q^{\sfrac{1}{8}}\\
\amp=\sqrt[8]{q}\amp\amp\text{by the } \knowl{./knowl/fact-rational-exponent-rule-i.html}{\text{Radicals and Rational Exponents Rule}}
\end{align*}
\begin{alignat*}{2}
3\left(c^{\sfrac{1}{2}}+d^{\sfrac{1}{2}}\right)^2\amp=3\left(c^{\sfrac{1}{2}}+d^{\sfrac{1}{2}}\right)\left(c^{\sfrac{1}{2}}+d^{\sfrac{1}{2}}\right)\\
\amp=3\left(\left(c^{\sfrac{1}{2}}\right)^2+2c^{\sfrac{1}{2}}\cdot d^{\sfrac{1}{2}}+\left(d^{\sfrac{1}{2}}\right)^2\right)\\
\amp=3\left(c^{\sfrac{1}{2}\cdot 2}+2c^{\sfrac{1}{2}}\cdot d^{\sfrac{1}{2}}+d^{\sfrac{1}{2}\cdot 2}\right)\\
\amp=3\left(c+2c^{\sfrac{1}{2}}\cdot d^{\sfrac{1}{2}}+d\right)\\
\amp=3\left(c+2(cd)^{\sfrac{1}{2}}+d\right)\amp\amp\text{by the } \knowl{./knowl/item-exponent-rules-product-to-a-power.html}{\text{Product to a Power Rule}}\\
\amp=3\left(c+2\sqrt{cd}+d\right)\amp\amp\text{by the } \knowl{./knowl/fact-rational-exponent-rule-i.html}{\text{Radicals and Rational Exponents Rule}}\\
\amp=3c+6\sqrt{cd}+3d
\end{alignat*}
\begin{align*}
3\left(4k^{\sfrac{2}{3}}\right)^{-\sfrac{1}{2}}\amp=\frac{3}{\left(4k^{\sfrac{2}{3}}\right)^{\sfrac{1}{2}}}\amp\amp\text{by the } \knowl{./knowl/item-exponent-rules-negative-exponent-definition.html}{\text{Negative Exponent Rule}}\\
\amp=\frac{3}{4^{\sfrac{1}{2}}\left(k^{\sfrac{2}{3}}\right)^{\sfrac{1}{2}}}\amp\amp\text{by the } \knowl{./knowl/item-exponent-rules-product-to-a-power.html}{\text{Product to a Power Rule}}\\
\amp=\frac{3}{4^{\sfrac{1}{2}}k^{\sfrac{2}{3}\cdot\sfrac{1}{2}}}\amp\amp\text{by the } \knowl{./knowl/item-exponent-rules-power-to-a-power.html}{\text{Power to a Power Rule}}\\
\amp=\frac{3}{4^{\sfrac{1}{2}}k^{\sfrac{1}{3}}}\\
\amp=\frac{3}{\sqrt{4}\sqrt[3]{k}}\amp\amp\text{by the } \knowl{./knowl/fact-rational-exponent-rule-i.html}{\text{Radicals and Rational Exponents Rule}}\\
\amp=\frac{3}{2\sqrt[3]{k}}
\end{align*}
Kepler's third law of motion says that for objects with a roughly circular orbit that the time (in hours) that it takes to make one full revolution around the planet, \(T\text{,}\) is proportional to three-halves power of the distance (in kilometers) from the center of the planet to the satellite, \(r\text{.}\) For the Earth, it looks like this:
Most satellites orbit in what is called low Earth orbit 4 en.wikipedia.org/wiki/Low_Earth_orbit, including the international space station which orbits at about 340 km above from Earth's surface. The Earth's average radius is about 6380 km. Find the period of the international space station.
The formula has already been identified, but the input takes just a little thought. The formula uses \(r\) as the distance from the center of the Earth to the satellite, so to find \(r\) we need to combine the radius of the Earth and the distance to the satellite above the surface of the Earth.